Efek Sinergis Kombinasi Ekstrak Etanolik Kayu Secang dan Rimpang Lempuyang pada Sel Kanker Payudara MCF-7 - Haryanti, Sari; Sholikhah, Ika Yanti M.; Widiyastuti, Yuli (Jurnal Kefarmasian Indonesia, 2019)
Cancer is one of critical, chronic, and complex disease, also becoming the high cause of death in the world. Brazilin and brazilein in sappan wood (Caesalpinia sappan L.) and zerumbone in bitter ginger rhizome (Zingiber zerumbet L.) are known having cytotoxic activity with different mechanisms. This study aimed to examine combination effect of sappan wood and bitter ginger rhizome. Sappan wood and bitter ginger rhizomes macerated with ethanol 96% for 3x24 hours, filtered, and evaporated to obtain dried extract.Cytotoxic effect on MCF-7 cells was done using MTT assay. Combination Index (CI) was determined by CompuSyn based on the result of cytotoxic combination. Cell cycle profile and apoptosis induction was analyzed by flow cytometry. Sappan wood extracts and bitter ginger rhizome exhibited cytotoxic effects on MCF-7 cells with the IC50 values of 30 and 155 μg/mL respectively. The combination of sappan wood 15 μg/mL and bitter ginger 8, 12, 24, and 60 μg/mL produced synergistic effect with the CI value of 0.57-0.85. Sappan wood 15 μg/mL combined with bitter ginger 8 and 24 μg/mL showed cell cycle inhibition at G2/M phase. The combination also increased apoptosis induction compared to untreated cells and its single treatment.The combination of sappan wood ethanolic extracts and bitter ginger rhizome showed synergistic cytotoxic effect. Its synergism effect revealed through cell cycle arrested at G2/M phase and acceleration of apoptotic induction.